Variabel-Variabel yang Memengaruhi Capaian Pembangunan TIK di Indonesia, Kawasan Barat Indonesia, dan Kawasan Timur Indonesia Tahun 2017-2022 - Adristi, Nadiva Fitri; Munaf, Alfatihah R.M.N.S.P. (Seminar Nasional Official Statistics, 2024)
Information and communication tehnology (ICT) has brought changes in various aspects of life. ICT development in Indonesia as measured by the ICT development index has increased every year. However, until 2022 the value is still in the range of 5, while the ICT development target in 2030 is 8.00 out of 10.00. ICT development in Indonesia also faces inequality between Western and Eastern Indonesia. This study aims to identify variables influencing ICT development in Indonesia, Western Indonesia, and Eastern Indonesia using panel data regression. The results showed that GDP per capita, the percentage of productive-age population, and COVID-19 pandemic can increase ICT development in Western Indonesia, Eastern Indonesia, and nationally. Population density can increase ICT development in Western Indonesia and nationally. The percentage of government spending on ICT can increase ICT development nationally. The percentage of households with access to electricity can increase ICT development in Western Indonesia.